Effects of Mindfulness practice on work stress: a study with professionals in Primary Health Care (Research, Society and Development, 2021)
The objective of this study is to evaluate the effect of a Mindfulness-based program on mindfulness levels and in the risk of illness associated with stress at work in primary health care (PHC) professionals in Ribeirão Preto, Brazil. This is a quasi-experimental study, with 26 PHC professionals, using quantitative methods and an analytical before and after approach of an 8-week Mindfulness Program. The intervention was evaluated applying the instruments: Five Facet Mindfulness Questionnaire and Job Stress Scale. There were significant differences in six Mindfulness facets after the intervention: Observe (p = 0.002); Describe (p = 0.01); Act with awareness - autopilot (p = 0.01) and distraction (p = 0.05); Non-reactivity to inner experience (p = 0.0005); Non-judgement of inner experience (p = 0.01); and in total Mindfulness scores (p = 0.0000018). Regarding the stress levels at work, the reduction of the organizational mode in high job strain was observed (before: 35%, after: 19%).  It is concluded that interventions based on Mindfulness applied to PHC professionals can improve the levels of mindfulness and modify the modes of organization at work, reducing the risk of illness associated with stress in these professionals.